Dispatches from the Village - Mabeza, Christopher M. (Book collections on Project MUSE., 2019)
In this book, Chris Mabeza takes the reader through a breath taking journey of the vicissitudes of village life in Zimbabwe from the colonial days to the present. This, at a time when telling African stories is enjoying a Risorgimento. Thus, in essence Mabeza "throws his fingers in the wind" and catches the zeitgeist of African storytelling. The stories leave the reader spellbound. Dispatches from the village has its finger on the pulse of the people. This gorgeous collection of short stories is a product of immersive thick descriptions of rural life as it intersects with urban life. The author grapples with the effects of what has generally been observed as the "brutish and nasty new normal". The rural landscape has not been spared the vagaries of this new normal. However, when overwhelmed by the tsunami of negative news that permeate our media, pick-up Dispatches from the village to soothe yourself.